PENERAPAN PEMBELAJARAN QUANTUM LEARNING DENGAN PERPADUAN ANTARA TEKNIK PEMETAAN PIKIRAN (MIND MAPPING) DAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X IPS 2 SMAN 8 MALANG SEMESTER GENAP TAHUN AJARAN 2014/2015 - Amanda Defi Nuraini; Sapir Sapir; Dwi Wulandari (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2015)
This study aimed to describe the application of Quantum Learning study with combination of Mind Mapping technique (Mind Mapping) and think pair share in the learning process, describe improving student learning outcomes, as well as describing the students' response to the application of learning. Research procedure includes pratindakan, the first cycle and the second cycle. Quantum Learning teaching and learning of the perpaduaan between mind mapping technique (Mind Mapping) and Think Pair Share to improve learning outcomes of economic class X IPS 2 SMAN 8 Malang can be applied in the learning process very well and have an impact on student learning outcomes. The results showed an increase in the percentage of student learning outcomes classical mastery of the first cycle to the second cycle of 27.3%. Completeness of student learning outcomes classical first cycle an average of 60.6%, the second cycle average rose to 87.9%. Student learning outcomes first cycle an average of 70.9 and the second cycle the average rose to 84.2. The application of this study received a positive response.